المشكلات التسويقية التي تواجه زراع الحنطة في قضاء تكريت بمحافظة صلاح الدين - العراق وعلاقته ببعض المتغيرات الزراعية - أرحيم، فراس إبراهيم (جامعة تكريت - كلية الإدارة والاقتصاد, 2018)
The target of research is to determine a marketing problems that faced wheat farmers in Tikrit district – salah alden Governorate – Iraq, as well as to know the link relationship between the marketing problems and the following independent variables (Agricultural plan, the Quantity of production, Agricultural land), Also to know a proposal about marketing problems, then to know marketing mechanism in Tikrit district – Salah Alden Governorate. The study society included 1125 farmers, I took 75 farmers comprise 15% of all farmers, and then I excluded the initial test sample. The Questionnaire was used to collect a data, it consist two parts, the first one included a variable study Data, and the second part included 23 clauses that used to measure a level of marketing problems. Then, we confirmed of virtual honesty. The Questionnaire stability is measured by Alpha Krunbkh way, which is (0.86). The results show a level of marketing problems is high, Also show there are negative significant relation between a marketing problems with (The Quantity of production and Agricultural land), and there are positive relation (non- significant) with Agricultural plan.
استهدف البحث تحديد مستوى المشكلات التسويقية التي تواجه المزارعين في قضاء تكريت بمحافظة صلاح الدين، والتعرف على علاقة الارتباط بين مستوى المشكلات التسويقية وبعض المتغيرات المستقلة الأتية (الخطة الزراعية، كمية الحاصل، المساحة المزروعة) وكذلك التعرف على أهم مقترحات وحلول المبحوثين حول المشكلات التسويقية التي تواجههم والتعرف على اليه عملية التسويق في قضاء تكريت. شمل البحث ٧٥ مبحوثا يشكلون ١٥% من مجموع المزارعين في قضاء تكريت البالغ عددهم ١١٢٥ مزارعا بعد استبعاد عينة الاختبار الأولي البالغة (٢٠) مبحوثا واستخدم الاستبيان أداة لجمع البيانات من المبحوثين مؤلفة من جزئيين: يتعلق الجزء الأول بالمعلومات الخاصة بالمتغيرات المدروسة واشتمل الجزء الثاني على ٢٣ فقرة لقياس مستوى المشكلات التسويقية وبعد التأكد من الصدق الظاهري لاستمارة الاستبيان تم قياس الثبات بطريقة كرونباخ الفا حيث بلغ (0.86). أظهرت النتائج أن مستوى المشكلات التسويقية عاليا، ووجدت علاقة ارتباط معنوية بين مستوى المشكلات التسويقية وكل من متغيرات المساحة المزروعة وكمية الحاصل وعلاقة موجبة غير معنوية مع متغير الخطة الزراعية، كاتبين وجود عدد من المقترحات والحلول من وجهة نظر المزارعين حول المشكلات التسويقية وتم التعرف على الية التسويق المتبعة في التسويق في القضاء، وأوصى الباحث بضرورة تسهيل اليه التسويق واستلام السايلوات للمحصول منذ بداية التسجيل للخطة الزراعية لحين التسويق وأستلام مستحقات المحصول.
Keywords: التسويق الزراعي -- المحاصيل الزراعية -- الإنتاج الزراعي -- التنمية الاقتصادية -- العراق